Neutrophil Extracellular Traps, Platelets and Endothelial Cells Cooperatively Contribute to Hypercoagulability in Non-Small Cell Lung Cancer - Tong, Dongxia; Gao, Yuan; Sun, Weihua; Yang, Jie; Liu, Yang; Li, Jihe; Zhang, Yan (Thrombosis and Haemostasis, 2024)
Thromboembolism is the second leading cause of death among patients with non-small cell lung cancer (NSCLC), but the precise mechanisms of thrombogenesis in NSCLC remain largely unknown. Our objectives were to evaluate the definitive role of neutrophil extracellular traps (NETs) in the hypercoagulability in NSCLC and to explore its interactions with platelets and endothelial cells (ECs).The levels of NET markers in samples from 100 NSCLC patients and 30 healthy controls were measured by ELISA. NET formation was detected using immunofluorescence. Procoagulant activity was assessed based on purified coagulation complex, thrombin, clotting time, and fibrin formation assays.The plasma levels of NETs were increased in a stage-dependent manner in NSCLC patients and were markedly higher than those in controls. Neutrophils from NSCLC patients were more prone to form NETs, resulting in shortened coagulation time, significantly increased thrombin–antithrombin complexes and fibrin compared to controls. Moreover, NETs generation was mediated by High Mobility Group Box 1 from activated platelets in NSCLC patients. Conversely, NETs from NSCLC patients also induce phosphatidylserine exposure on platelets, leading to markedly enhanced procoagulant activity (PCA). Furthermore, NETs can damage endothelial cells and convert them to a procoagulant phenotype. The administration of NETs inhibitors (DNase I/activated protein C) could markedly diminish the PCA of NETs, activated platelets, and ECs.Our results suggest that NETs contribute to hypercoagulability and may represent a potential therapeutic target to prevent cancer-associated thrombosis in NSCLC patients.
Keywords: neutrophil extracellular traps; non-small cell lung cancer; platelet; endothelial cells; procoagulant activity